Reconceptualizing a college chemistry course to improve teaching and learning. - Gallos, Marilou R. (Curtin University, 2002)
This thesis describes the process of course and faculty development in college chemistry at the University of San Carlos in the Philippines. The aim of the research was to increase intellectual engagement through the implementation of a simple instructional cycle to replace a dominant lecture approach. The cycle consisted of three phases: (a) a plenary which is a short presentation of the subject matter, (b) seatwork activity where students work on problems, questions or activities with the instructor moving around the classroom, and (c) closure or summary which includes reactions to learning difficulties encountered by the instructor during phase b. The approach was designed to improve basic teaching skills and to enhance instructors' knowledge of student learning problems. The research employed qualitative and quantitative methods utilising multiple sources of data collection. Validation and reliability criteria were addressed through pluralistic epistemologies; triangulation, use of external observers, member checks, peer commentaries, and case studies. Likewise, the instructors' adaptation to the three phases in the approach were analysed together with students' perceptions of the teaching approaches in the new course. Two instructors, who were involved in the case study, taught the first version of the course having been coached by the researcher who attended almost all lessons within the semester. Analysis of the data indicated that the instructors developed teaching skills applicable in this instructional cycle approach. Problems in the implementation of the cycle were identified and used as the basis for the reconceptualization of a year-long, departmental study involving 13 instructors each of whom applied the instructional cycle to some degree.Three instructors were able to significantly change their teaching and apply meaningful student seatwork in their lessons. Nine instructors, who were moderately successful implementers, exhibited some pedagogical growth but still had problems in maintaining a well-organised classroom environment. The other three instructors had considerable trouble in applying the new approach. The shift from lecturing to applying the instructional cycle might seem like a relatively small change, yet it is a huge step for instructors who have predominantly taught using lectures for over ten years. This situation called for support by effective intervention through a realistic and practical faculty development program. After an initial training of instructors, extensive coaching in the classroom was used during the implementation phase as well as weekly small group meetings and monthly large group seminars. The course and faculty development process led to a strong increase in chemistry and chemistry pedagogy discussions in the faculty room with increasing collegiality. After the initial implementation, the process of change has continued. Every semester more improvements are made and several other Chemistry courses have been revised using the instructional cycle model of instruction.